Wear prediction of friction material and brake squeal using the finite element method - Abu Bakar, A. R.; Ouyang, Huajiang (Elsevier, 2008)
This paper presents wear prediction of friction material in a disc brake assembly. A new and unworn pair of brake pads is tested under different durations of brake application to establish wear on their surfaces. One of the wear models available in the literature is adopted and then modified to suit the current work. A detailed three-dimensional finite element (FE) model of a real disc brake is developed considering the real surface topography of the friction material. Confirmation of the adopted model is made between predicted and measured static contact pressure distribution and surface topography of the friction material. Predicted unstable frequency and experimental squeal frequency are shown to be in fairly good agreement.